UKURAN PERUSAHAAN, DEWAN KOMISARIS DAN ENVIRONMENTAL DISCLOSURE - Effendi, Bahtiar (JURNAL RISET AKUNTANSI TIRTAYASA, 2018)
The research at examining the influence of firm size, board of commissioners, such as board of commissioners size, proportion of independent commissioners, the commissioner president’s educational background, and the number of commissary chamber meeting on the environmental disclosure in manufacture companies listed in Indonesian Stock Exchange.The population of this research is all of public manufacture companies in the year 2008-2014 The samples of this research are 26 of public manufacture companies, which selected by purposive sampling method. This research data were colected from Indonesian Stock Exchange (IDX) from 2008 until 2014 and also from each company`s website.The research using multiple regression analysis as the research method and the result from this research show that is no influence between commissioners size, proportion of independent commissioners and the commissioner president’s educational background with environmental disclosure, and the firm size and the number of commissary chamber meeting influence positive. Keywords: Firm Size, Board of Commissioners Size, Proportion of Independent Commissioners, The Commissioner President’s Educational Background, The Number of Commissary Chamber Meeting, Environmental Disclosure.